Trial protocol: a randomised controlled trial to verify the non-inferiority of a partially covered self-expandable metal stent to an uncovered self-expandable metal stent for biliary drainage during neoadjuvant therapy in patients with pancreatic cancer with obstructive jaundice (PUN-NAC trial). Issue 7 (8th July 2021) - Kuwatani, Masaki; Kawakubo, Kazumichi; Sugimori, Kazuya; Inoue, Hiroyuki; Kamada, Hideki; Ishiwatari, Hirotoshi; Kato, Shin; Iwashita, Takuji; Yoshida, Makoto; Hashimoto, Shinichi; Itonaga, Masahiro; Mizukami, Yusuke; et al.
Abstract : Introduction: Neoadjuvant chemotherapy or neoadjuvant chemoradiotherapy (NAC/NACRT) for resectable/borderline resectable pancreatic cancers was recently performed to improve clinical outcomes and led to good results, although it remains controversial whether NAC/NACRT is beneficial for resectable pancreatic cancer. A few recent studies revealed longer patency and lower cost related to the stent occlusion of a metal stent than those of a plastic stent during NAC/NACRT. It also remains controversial which type of self-expandable metal stent (SEMS) is the most suitable for patients with resectable/borderline resectable pancreatic cancer during NAC/NACRT: an uncovered SEMS (USEMS), a fully covered SEMS (FCSEMS) or a partially covered SEMS (PCSEMS). So far, two randomised controlled trials indicated that a USEMS and an FCSEMS were similar in preoperative stent dysfunction and adverse event rate. Thus, we aimed to verify the non-inferiority of a PCSEMS to a USEMS in this multicentre randomised controlled trial. Methods and analysis: We designed a multicentre randomised controlled trial, for which we will recruit 100 patients with resectable/borderline resectable pancreatic cancer and distal biliary obstruction scheduled for NAC/NACRT from 13 high-volume institutions. Patients will be randomly allocated to the PCSEMS group or USEMS group. The primary outcome measure is the preoperative biliary event rate. Data will be analysed after completion of the study. We will calculate the 95% CIs of the incidence of preoperative biliary events in each group and analyse whether the difference between them is within the non-inferiority margin (10%). Ethics and dissemination: This study has been approved by the institutional review board of Hokkaido University Hospital. The results will be submitted for presentation at an international medical conference and published in a peer-reviewed journal. Trial registration number: UMIN000041737; jRCT1012200002.